Comprehensive Experimental Study on the Thermophysical Characteristics of DI Water Based Co0.5Zn0.5Fe2O4 Nanofluid for Solar Thermal Harvesting - Tsogtbilegt Boldoo; Jeonggyun Ham; Honghyun Cho (Energies, 2020)
The thermophysical properties of water-based Co0.5Zn0.5Fe2O4 magnetic nanofluid were investigated experimentally. Consequently, the viscosities of 0.25 wt% and 1 wt% Co0.5Zn0.5Fe2O4 nanofluid were 1.03 mPa∙s and 1.13 mPa∙s, each greater than that of the 20 °C base fluid (water), which were increased by 7.3% and 17.7%, respectively. The Co0.5Zn0.5Fe2O4 nanofluid thermal conductivity enhanced from 0.605 and 0.618 to 0.654 and 0.693 W/m·°C at concentrations of 0.25 wt% and 1 wt%, respectively, when the temperature increased from 20 to 50 °C. The maximum thermal conductivity of the Co0.5Zn0.5Fe2O4 nanofluid was 0.693 W/m·°C at a concentration of 1 wt% and a temperature of 50 °C. Furthermore, following a solar exposure of 120 min, the photothermal energy conversion efficiency of 0.25 wt%, 0.5 wt%, 0.75 wt%, and 1 wt% Co0.5Zn0.5Fe2O4 nanofluids increased by 4.8%, 5.6%, 7.1%, and 4.1%, respectively, more than that of water.